2016
DOI: 10.1111/ruso.12098
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, Place, and Coal Employment across Appalachia and the United States in a New Economic Era

Abstract: The impacts of employment in the coal industry remain controversial. Few studies have investigated these impacts over the decade of the great recession and in light of the nation's changing energy economy. We bring together two long-standing rural sociological traditions to address debates framed at the national level and for Appalachian communities facing the throes of transition from the coal industry. Building from rural sociology's "poverty and place" tradition and from natural resources sociology, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 50 publications
(78 reference statements)
0
80
0
Order By: Relevance
“…However, there is no nationally comprehensive and widely accepted alternative poverty measure available. The Small Area Income estimates are model based yet correlate very strongly with poverty estimates from the decennial census, suggesting that they are close approximations of actual poverty rates as measured by official criteria (Lobao et al 2016). Note, also, that many of the control variables used in other analyses (e.g., racial or age composition) are not available for all the years under study in this article.…”
Section: Dependent Variablesmentioning
confidence: 82%
See 2 more Smart Citations
“…However, there is no nationally comprehensive and widely accepted alternative poverty measure available. The Small Area Income estimates are model based yet correlate very strongly with poverty estimates from the decennial census, suggesting that they are close approximations of actual poverty rates as measured by official criteria (Lobao et al 2016). Note, also, that many of the control variables used in other analyses (e.g., racial or age composition) are not available for all the years under study in this article.…”
Section: Dependent Variablesmentioning
confidence: 82%
“…Freudenburg and Wilson (2002) reviewed 301 previous studies examining the socioeconomic performance of mining communities from the 1970s to the 1990s and concluded that overall, the research did "not support the widespread expectation that mining can be expected to increase the prosperity of isolated rural communities" (571). On the other hand, Lobao et al (2016) report that the effect of coal mining on socioeconomic well-being in Appalachia varies by decade, with some positive effects in recent years.…”
Section: Natural Resource Dependency and The Resource Cursementioning
confidence: 99%
See 1 more Smart Citation
“…To assess the spatiotemporal dynamics characteristic of our data structure and of substantive relevance to our research question, we develop a new data-analytical method that accounts for both aspects of autocorrelation and is feasible and practical for accommodating the added complexity of a space-time interaction. In doing so, our study contributes to this journal's tradition of developing and applying advanced spatial regression models to sociological and demographic research (e.g., Brasier 2005;Brown et al 2011;Chi 2010;Deller and Deller 2012;Lobao et al 2016;Peters 2012).…”
Section: Analytical Strategymentioning
confidence: 97%
“…Therefore, I conceive of a resource-based environmental inequality study that incorporates empirical and theoretical evidence from rural, resource, and environmental sociology to study the distribution of resource-extraction-related hazards. This line of research is especially important in regions like Appalachia where environmental hazards created by a declining coal industry threaten prospects for economic development in the region (Lobao et al forthcoming;Todd, Doshi, and McInnis 2010).…”
Section: Environmental Inequalitymentioning
confidence: 99%